Schism China, America and the fracturing of the global trading system - Blustein, Paul. (Waterloo Centre for International Governance Innovation, 2019)
China's entry to the World Trade Organization (WTO) in 2001, following years of negotiations, resulted in profound changes--both good and bad--for China, for its trading partners (particularly its most important, the United States) and for the global trading system as a whole. Journalist Paul Blustein weaves a compelling story based on interviews with many of the participants involved in the negotiations and subsequent WTO trade disputes involving China. He incorporates information from news reports, written briefs, oral presentations, internal White House memoranda and other published material, to detail the process, events and individuals involved in China's bid to join the WTO and the developments that followed. Efforts by non-Chinese officials and political actors to address Beijing's most problematic policies, with the United States taking a lead role, are recounted; the book also examines the parts played by multilateral institutions, specifically the WTO and the International Monetary Fund. The phenomenon of the "China shock" and the evolution of "China Inc." are examined. The author maintains that integrating China into the global economy presented an immense challenge to the international community, and although the WTO has been far from perfect, the process has gone much more smoothly, from a global standpoint, than it would have otherwise. The narrative culminates in the Sino-US trade war and related events of 2018-2019 that have brought the trading system to a breaking point
Includes bibliographical references.
Keywords: World Trade Organization